Pengembangan Modul Matematika Kontekstual Dan Penemuan Terbimbing Untuk Meningkatkan Eq Siswa Akselerasi - Yhasinta Agustyarini (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2017)
The aim of this study produces contextual and guided inquiry mathematics module to increase EQ of acceleration students and describe the quality of the developed product. This research is a developmental research with adapted from Borg & Gall, Dick, Carey, & Carey and Plomp. The research through several phases: (1) preliminary investigation, (2) design, (3) realization/construction, (4) test, evaluation, and revision, and (5) implementation. Subjects of trial-test in this research are the eight grade students of MTs Unggulan Amanatul Ummah Surabaya with acceleration programe. Data collected are data about the product quality which is developed, i.e. validity, practicality, and effectivity. The result of the test shows that more than 80% of the student achieve the minimum score and percentage many of students who are at a high minimum and very high minimum category increase on EQ questionnaire. The research produced mathematics module and supporting components, consisting of valid, practical, and effective syllabuses, lesson plans, mathematics module, and the valid, practical, and reliable of test.